Synergy of Authority and Innovation of Female Village Heads' Leadership in Creating Advanced and Competitive Villages (Case Study of Ketegan Village, Pasuruan) - Irsyadiyah, Azizatun Nisa’; Thohir, Muhammad; Mardiyah, Mardiyah (Jurnal Pengabdian Nusantara, 2024)
Based on the Indonesian Nutrition Status Survey (SSGI) in 2022, the This study evaluates the leadership of the female village head of Ketegan Village in building synergy of authority and innovation to realize an advanced and competitive village. Through a qualitative approach and case study, the results show that the participatory leadership of the village head has succeeded in increasing community participation and advancing village development. The three pillars of leadership used play an important role in building solidarity between the village government and the community.